Etnobotani : Pemanfaatan dan Makna Simbolik Daun Sirih pada Masyarakat Batak Toba, Desa Ugan-Ugan, Samosir - Ririn Natasha Marbun; Fadly Husain (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Betel leaf (Piper Betle L.) is one of the plants that has many benefits and symbolic meanings in the lives of the Toba Batak tribe in Ugan-Ugan Village, Sibonor Ompu Ratus Subdistrict, Nainggolan District, Samosir Regency, North Sumatra. Betel leaf is an example of local wisdom that has been preserved for generations as being a cultural symbol with meaning. This article aims to explore various aspects of the use of betel leaves in health, culture, and social life among the Batak Toba tribe, the symbolic meaning of betel leaves, and the reasons why the Batak Toba tribe considers betel leaves so important that they are widely used. This study uses qualitative methods with observation, documentation, and in-depth interviews with the community, including the elderly, parents, and Raja Parhata, to obtain information related to the understanding of the use and meaning of betel leaves. The results of this study show that the Batak Toba tribe makes extensive use of betel leaves in traditional medicine. Betel leaves are also the most important element in traditional ceremonies. The Batak Toba community believes that betel leaves or demban are very important and sacred to them for every traditional ceremony. Betel leaves or demban are a symbol of blessing for them and a prayer to be kept away from danger so that the traditional ceremonies carried out can be blessed and run smoothly until the end. This study confirms that betel leaves form a “web of significance” that integrates health, tradition, and spirituality. These findings show that traditional medicine and traditional symbols are inseparable in the local knowledge system of the Batak Toba people and contribute to cultural preservation and sustainable development based on local wisdom.